The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/adfm.202006639
|View full text |Cite
|
Sign up to set email alerts
|

Untethered Feel‐Through Haptics Using 18‐µm Thick Dielectric Elastomer Actuators

Abstract: Head-mounted displays for virtual reality (VR) and augmented reality (AR) allow users to see highly realistic virtual worlds. The wearable haptics that enable feeling and touching these virtual objects are typically bulky, tethered, and provide only low fidelity feedback. A particularly challenging type of wearable human-machine interface is feel-through haptics: ultra-thin wearables so soft as to be mechanically imperceptible when turned off, yet generating sufficient force when actuated to make virtual objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
138
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 46 publications
0
138
0
Order By: Relevance
“…The surface texture, topography, stiffness, deformation, applied force, and other desired information of the internal organs of the patient can be measured and fed back by the integrated sensing system of the surgical tools and then transmitted to the surgeon through tactile reproduction provided by the soft actuator array. Some researches using soft robotic technologies for haptic feedback have emerged in recent years, and a recent review of them can be found in the study by Yin et al [408] Common haptic feedback methods based on mechanical stimulation include vibrotactile stimulation, [409,410] normal pressing, [411,412] and skin stretch, [413,414] and the introduction of soft technologies can achieve safe, compact, and lightweight system integration as well as good simulation of tactile sensation of soft organs.…”
Section: Robotic Assistancementioning
confidence: 99%
“…The surface texture, topography, stiffness, deformation, applied force, and other desired information of the internal organs of the patient can be measured and fed back by the integrated sensing system of the surgical tools and then transmitted to the surgeon through tactile reproduction provided by the soft actuator array. Some researches using soft robotic technologies for haptic feedback have emerged in recent years, and a recent review of them can be found in the study by Yin et al [408] Common haptic feedback methods based on mechanical stimulation include vibrotactile stimulation, [409,410] normal pressing, [411,412] and skin stretch, [413,414] and the introduction of soft technologies can achieve safe, compact, and lightweight system integration as well as good simulation of tactile sensation of soft organs.…”
Section: Robotic Assistancementioning
confidence: 99%
“…For wearable assistance in particular, research has mainly explored communication and rehabilitation. As haptic feedback is an important part of electronic textiles and wearable technologies, integrating DE tactile actuators into wearable systems through haptic sensation has been a rising field of interest attributed to material softness, small size, ease of fabrication, and adaptability compared to traditional rigid motors with fixed frequencies [98]. A crucial factor for effective sensing of haptic cues is skin perceptibility, which means the output force and resonance frequency should reach perceivable levels and depends on both human and device factors, such as placement on bodies and material stiffness [98,99].…”
Section: Applicationsmentioning
confidence: 99%
“…As haptic feedback is an important part of electronic textiles and wearable technologies, integrating DE tactile actuators into wearable systems through haptic sensation has been a rising field of interest attributed to material softness, small size, ease of fabrication, and adaptability compared to traditional rigid motors with fixed frequencies [98]. A crucial factor for effective sensing of haptic cues is skin perceptibility, which means the output force and resonance frequency should reach perceivable levels and depends on both human and device factors, such as placement on bodies and material stiffness [98,99]. For example, typically finger tips are ideal positions of tactile devices due to their higher sensitivity than other parts like arms, and usually susceptible to a force threshold around 30mN depending on the fingers [100].…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations